Rehabilitation of Jenin-Haifa Road - Adan Ateeq; Rawan Badad (My University, 2018)
Jenin-Haifa Road is one of the main roads in Jenin Governorate which extends about 11 km from Salem border crossing to the center of Jenin City. It connects many towns and villages of Jenin Governorate with Jenin City, such as Burqin, Kafr Dan, Al-Yamoun, and others. Its importance comes from being a main link between Palestine and the area beyond the green line. The road consists mainly from two sections; the first is an urban section which extends a specific distance inside Jenin City, and the second is a rural section extends outside the city limits. In this project, the rural section of the road has been studied since it faces a lot of traffic and road pavement problems, such as poor infrastructure due to the agricultural soil. Also, there is a problem in the drainage system at specific regions within the facility, in addition to some problems in the geometric design. Finally, the problem which citizens suffer from the most is the lack of safety. This project aims to evaluate the current situation of the road, to provide applicable solutions for each problem and to prepare a design for rehabilitation of the road. In order to do that, governmental and private institutions have been visited to get the available existing data. Also, an overall site investigation has been done to explore the current status and collect data that has been analyzed later. Traffic analysis has been conducted, soil investigation has been done, a minor safety study has been conducted and design criteria have been identified, in preparation for design process. A geometric design has been proposed, including horizontal and vertical alignment, typical cross section and intersections design, and it followed with quantity surveying and cost estimation.